Kinerja Jabatan Fungsional Perekayasa di Lingkungan Pusat Penelitian dan Pengembangan Jalan dan Jembatan - Suhendar (Coopetition : Jurnal Ilmiah Manajemen, 2018)
The results of research on the Performance of Functional Position of Engineers in the Environment of Center of Research and Development of Road and Bridge, showed that: (1) Leadership variable (X1) has a strong positive effect on performance of functional position of engineer (Y) equal to 36,5%. (2) The compensation variable (X2) has a positive but very weak effect on the performance of the functional position of the engineer (Y) of 3%. (3) Leadership and compensation variables affect simultaneously to the performance, with correlation coefficient R = 0.612 or determinant R2 of 0.375 or 37.5%. Thus, leadership and compensation should be able to create boosting working conditions personal comfort or environmental factors that will improve employee performance.